THE EMPIRICAL RESEARCH OF THE EXPERIENCE OF REFLECTION OF FUTURE PSYCHOLOGISTS - Tabachnikov, Stanislav; Mikhalchuk, Natalia; Kharchenko, Yevgenii; Ivashkevych, Eduard (Psychological Prospects Journal, 2019)
The article deals with four types of competence that facilitate the development of the experience of reflection of future psychologists: 1) a special competence is the possession of our own professional activities at a sufficiently higher level, the ability of the person to design their further professional development; 2) a social competence is the possession of joint (group, co-operative) professional activity, cooperation, and it was also adopted by these professional methods, such as the methods of professional communication; a social competence is a social responsibility for value of the results of our work; 3) a personal competence is a possession of methods of personal presentation and self-development, means of confrontation with professional deformations of a person; 4) the individual competence is a possession of methods of self-realization and a process of the development of the individuality within the profession, readiness for professional growth, ability to individual self-preservation, resistance to professional burnout, ability to organize our work rationally, not overloading in time, carrying out activities with positive motivation, joy and energy.It was shown that individual experience had valuable, reflexive, communicative, operational characteristics. It is this set of parameters of experience that ensures the independence of the psychologist, his purposeful activity. The results of the experimental studying, which was conducted during the training of future psychologists of experimental groups at higher school during the 2017, were described. With the students of experimental groups we organized training «Development of Interpretative Competence». At the end of each lesson, the method of narratives was used to refute students’ own activities, to reconstruct them with the actual meaning of their experiences, to illuminate and understand the essence and origin of the actual functioning of interpretative processes.